(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this manuscript, we present new ideas concerning the domain of soft BCK/BCI-algebras and outline specific categorical frameworks, including equalizers and finite products. Additionally, we demonstrate that the category of soft BCK/BCI-algebras conforms to a topological construct. Moreover, we establish that the category of soft BCK/BCI-algebras features distinctive elements such as terminal objects, initial objects, and zero objects.